Penerapan Metode Cooperative Integrated Reading and Composition (CIRC) dalam Peningkatan Kemampuan Siswa Memahami Teks Bahasa Arab - Maratusolikah Maratusolikah; Sopwan Mulyawan; Nanin Sumiarni (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2020)
This study aims to determine the extent of the influence of the use of CIRC Methods to the reading Arabian text ability of 10th grade students in public high school 2 Cirebon. The CIRC method in terms of language can be interpreted as a cooperative learning method that integrates a reading thoroughly and then compositing it into important parts.The main focus of this method is to make the use of time more effective. Learners are conditioned in cooperative teams that are then coordinated with the teaching of reading groups, so as to fulfill their objectives such as reading comprehension. So learners are motivated to cooperate with each other in a team. This research uses quantitative methods with the type of Quasi Experiment method and the design of the Nonequivalent Control group Design Research. The method of data collection in this study using documentation, interviews and tests, the sample is a Grade 10thÂ students of MAN 2 Cirebon divided into two classes, while the sampling technology using the Cluster Random Sampling and researchers took the grade 10 students of IPS 5 and students of Grade 10 IPS 1 as the control class. The pre-test result of 32 students has an average value of 53 and the post-Testnya value has an average value of 85, it shows a difference in the average value of 86. While the result of the Paired Sample T Test shows the value t =-5.765, df = 92, alpha = 0.05 and the test result Sig. (2-tailed) shows 0 ØŒ 00 < 0 ØŒ 05.